Co-delivery of etoposide and cisplatin in dual-drug loaded nanoparticles synergistically improves chemoradiotherapy in non-small cell lung cancer models. (1st April 2021) - Zhang, Maofan; Hagan, C. Tilden; Foley, Hayley; Tian, Xi; Yang, Feifei; Au, Kin Man; Mi, Yu; Medik, Yusra; Roche, Kyle; Wagner, Kyle; Rodgers, Zachary; Min, Yuanzeng; et al.
Abstract: Chemoradiotherapy with cisplatin and etoposide is a curative management regimen for both small and non-small cell lung cancers. While the treatment regimen is effective, it also has a high toxicity profile. One potential strategy to improve the therapeutic ratio of chemoradiation is to utilize nanotherapeutics. Nanoparticle formulation of cisplatin and etoposide, however, is challenging due to the significant mismatch in chemical properties of cisplatin and etoposide. Herein we report the formulation of a polymeric nanoparticle formulation of cisplatin and etoposide using a prodrug approach. We synthesized a hydrophobic platinum prodrug, which was then co-delivered with etoposide using a nanoparticle. Using mouse models of lung cancer, we demonstrated that dual-drug loaded nanoparticles are significantly more effective than small molecule chemotherapy in chemoradiotherapy. These results support further investigation of nanoparticle-based drug formulations of combination chemotherapies and the use of nanotherapeutics in chemoradiotherapy. Statement of Significance: The treatment of lung cancer often involves a combination of chemotherapy and radiation. While it can be effective, it also has a high toxicity profile. Preferential delivery of chemotherapeutics to the tumor while avoiding normal tissue would improve efficacy and lower toxicity. While this is challenging with conventional drug delivery technologies, nanotechnology offers a unique opportunity. In this study, we have engineered nanoparticles that are loaded with combination chemotherapeutics and showed such nanotherapeutics are more effective and less toxic than free chemotherapeutics in chemoradiotherapy. Our work highlights the importance and potential of nanoformulations of combination chemotherapy in chemoradiotherapy and cancer treatment. This approach can be translated clinically and it can have a significant impact on cancer treatment. Graphical abstract: Image, graphical abstract